My Scientology movie [videorecording (DVD)] - Dower, John; Dower, John; Theroux, Louis; Theroux, Louis; Rathbun, Mark <U+2019>Marty<U+2019>; Gehrt, Chris (Magnolia Home Entertainment, 2019)
Through dramatic reconstruction of incidents experienced by former members of the Church of Scientology, examines the controversy surrounding Scientology and what goes on behind the scenes of the church.